Electrotechnological methods for improving the quality of vegetable oils - Chervinskyy, L.; Radko , I. (Energy and Automation, 2025)
The methods of extracting oil from plant materials differ somewhat depending on the nature of the raw material and the content of the oil itself (oil). That is why, for many centuries, various methods of extracting oil from plant raw materials have been used: treatment of specially prepared oil raw materials with organic solvents, settling, centrifugation, distillation and filtration. The main methods today are: mechanical extraction, chemical extraction, supercritical fluid extraction, steam distillation and vacuuming. Recent studies have established that the least energy-consuming and promising are electrophysical methods of processing raw materials, based on the use of electromagnetic energy. In particular, the application and effectiveness of electrophysical methods of processing oil raw materials in improving the quality of purification and productivity of vegetable oils production are substantiated. Key words: vegetable oils, efficiency improvement, electrophysical purification methods